Effects of Black Pepper (), Turmeric Powder () and Coriander Seeds () and Their Combinations as Feed Additives on Growth Performance, Carcass Traits, Some Blood Parameters and Humoral Immune Response of Broiler Chickens - R. Abou-Elkhair; H. A. Ahmed; S. Selim (Asian-Australasian Journal of Animal Sciences, 2014)
Different herbs and spices have been used as feed additives for various purposes in poultry production. This study was conducted to assess the effect of feed supplemented with black pepper (Piper nigrum), turmeric powder (Curcuma longa), coriander seeds (Coriandrum sativum) and their combinations on the performance of broilers. A total of 210 (Cobb) one-d-old chicks were divided into seven groups of 30 birds each. The treatments were: a control group received no supplement, 0.5% black pepper (T1), 0.5% turmeric powder (T2), 2% coriander seeds (T3), a mixture of 0.5% black pepper and 0.5% turmeric powder (T4), a mixture of 0.5% black pepper and 2% coriander seed (T5), and a mixture of 0.5% black pepper, 0.5% turmeric powder and 2% coriander seeds (T6). Higher significant values of body weight gain during the whole period of 5 weeks (p<0.001) were observed in broilers on T1, T3, T5, and T6 compared to control. Dietary supplements with T1, T2, T3, and T6 improved the cumulative G:F of broilers during the whole period of 5 weeks (p<0.001) compared with control. The dressing percentage and edible giblets were not influenced by dietary supplements, while higher values of relative weight of the liver (p<0.05) were obtained in T5 and T6 compared to control. The addition of feed supplements in T5 and T6 significantly increased serum total protein and decreased serum glucose, triglycerides and alkaline phosphatase concentrations compared with the control group (p<0.05). Broilers on T6 showed significant decrease in the serum glutamate pyruvate transaminase concentration (p<0.05) compared to control. The broilers having T5 and T6 supplemented feed had relatively greater antibody titre (p<0.001) at 35 d of age than control. It is concluded that dietary supplements with black pepper or coriander seeds or their combinations enhanced the performance and health status of broiler chickens.